Kontribusi Alumi Pondok Pesantre Kontribusi Alumni Pondok Pesantren dalam Pembentukan Nilai-Nilai Islami di Masyarakat Parit Nipah Desa Melai - Muhammad Taufik (Akademika : Jurnal Keagamaan dan Pendidikan, 2025)
The instillation of Islamic values in society is vulnerable to deviation, making the role of alumni of Islamic boarding schools (ponpes) with upright beliefs crucial. This qualitative research in Melai Village, Meranti Islands, shows that the community's religious understanding has been formed, following Shafi'i fiqh, Imam Ghazali's Sufism, and Ash'ari's creed. Alumni of the Islamic boarding school (ponpes) contribute significantly to strengthening these values by serving as primary sources of reference. They actively organize religious activities such as dhikrul ghofilin (remembrance of God), Quran recitation, leading tahlil (religious recitation), and providing guidance through religious study groups (masjid taklim) and teaching the Quran. Furthermore, they also participate in community structures, such as serving as neighborhood association (RT) and community unit (RW) administrators, to ensure the implementation of Islamic values in daily life.